Women's mental health in Mozambique: is maternity a protective factor? - Saida Khan; Pamela Scorza; Kathryn L. Lovero; Palmira dos Santos; Wilza Fumo; Barbara Camara; Maria A. Oquendo; Milton L. Wainberg; Marcelo Fejo; Cristiane S. Duarte (Cambridge Prisms: Global Mental Health, 2022)
Abstract Backgroud Globally, women have been shown to have high rates of common mental disorders (CMDs). In low and middle-income countries (LMICs), women face significant challenges related to maternity. However, no study has compared mental health problems among pregnant/post-partum women, childless women of childbearing age, and women with children in a low-income country. We sought to compare the frequency of CMD and suicide risk in a sample of women presenting or accompanying patients in primary care in two Mozambican semi-urban settings.